Strategi Ahmad Dahlan dalam Modernisasi Pendidikan Islam Muhammadiyah - Sandi Setiawan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study explores the pivotal role of K.H. Ahmad Dahlan in founding and developing Muhammadiyah and his contributions to the modernization of Islamic education in Indonesia. The objective is to understand Ahmad Dahlan's strategies for purifying Islamic teachings and Muhammadiyah's efforts to modernize the educational system. The research methodology employed is a literature review, which involves gathering relevant information from various sources such as books, scholarly journals, and previous research reports. The findings indicate that Muhammadiyah, under Ahmad Dahlan's leadership, implemented modern educational management practices including planning, organizing, actuating, controlling, and evaluating. These practices successfully enhanced the quality of education by integrating religious and general knowledge, and by introducing more interactive and effective teaching methods and media. Regular evaluations and a robust organizational structure ensure that Muhammadiyah's educational programs continue to adapt to contemporary needs. The study concludes that Muhammadiyah's innovations and effective management have significantly improved the quality of Islamic education in Indonesia.